RƏQƏMSAL TRANSFORMASİYA - Pənahova İlkanə Mübariz qızı (Foundations and Trends in Research, 2024)
Super smart society: It refers to the whole of smart urbanization with its economic development structure, which includes all human and environmentalbased improvements such as education, health, daily life, safe city formations. It covers a wide range of city/human model that enables objects to connect with people and living things, reflects the intelligent and technological architectural formation and provides the cycle of many communications such as big data and artifical intelligence. Economic and social new learning, such as learning types developed using artificial intelligence technology, digital identity integrations and some digital culture practices, are seen as the main factors that make the processes of reaching a süper smart society. This relationship of needs, which creates cultural transformations and new economic models, creates new living standards and breakthroughs such as planned thinking strategies for the future